Three essays in applied microeconomic theory - Fagandini, Paulo (2018)
In this thesis, I write about the theory of contracts and auctions. In the fi rst two chapters, I study the principal-agent relationship with moral hazard. The fi rst chapter focuses on the matching between principals and agents, while the second analyzes the implications of the agent having a chance to x a potential bad outcome before it is revealed to the principal. Finally, in the third chapter, my coauthor and I model fi rst-price sealed-bid auctions, from an ex-ante perspective, to help bidders prepare bids in practice. We study how asymmetries in valuation, information, and sophistication of rivals affect the optimal strategy.